Sensitivity of maize hybrids to common smut under field artificial inoculation conditions - Frommer, Dóra; Veres, Szilvia; Radócz, László (Acta Agraria Debreceniensis, 2017)
Common smut disease of maize is one of the most frequent diseases of crop. In the last decades the importance of disease has decreased in feeding maize production, however its importance increasing again nowadays, especially at sweet maize hybrids. The aims of this work was to find hybrids possess of resistance, and to evaluate which ones are more or less susceptible under field artificial inoculation circumstances. Among feeding maizes the less susceptible hybrid was ‘P9578’, and the most susceptible ’NK Columbia’ hybrid, and differences in cob infection between them was significant (8.8%). At sweet corn hybrids the less susceptible was ’Prelude’, while the most susceptible was ’Jumbo’ with very high significant 74.6% differences.